Enzymatic synthesis of novel purine nucleosides bearing a chiral benzoxazine fragment. (20th January 2019) - Eletskaya, Barbara Z.; Gruzdev, Dmitry A.; Krasnov, Victor P.; Levit, Galina L.; Kostromina, Maria A.; Paramonov, Alexander S.; Kayushin, Alexei L.; Muzyka, Inessa S.; Muravyova, Tatyana I.; Esipov, Roman S.; Andronova, Valeria L.; Galegov, Georgiy A.; et al.
Abstract: A series of ribo‐ and deoxyribonucleosides bearing 2‐aminopurine as a nucleobase with 7, 8‐difluoro‐ 3, 4‐dihydro‐3‐methyl‐2H‐[1, 4]benzoxazine (conjugated directly or through an aminohexanoyl spacer) was synthesized using an enzymatic transglycosylation reaction. Nucleosides3 ‐6 were resistant to deamination under action of adenosine deaminase (ADA) Escherichia coli and ADA from calf intestine. The antiviral activity of the modified nucleosides was evaluated against herpes simplex virus type 1 (HSV‐1, strain L2). It has been shown that at sub‐toxic concentrations, nucleoside ( S )‐4‐[2‐amino‐9‐(β‐ D ‐ribofuranosyl)‐purin‐6‐yl]‐7, 8‐difluoro‐3, 4‐dihydro‐3‐methyl‐2 H ‐[1, 4]benzoxazine exhibit significant antiviral activity (SI > 32) on the model of HSV‐1 in vitro, including an acyclovir‐resistant virus strain (HSV‐1, strain L2/R). Abstract : A series of ribo‐ and deoxyribonucleosides bearing 2‐aminopurine as a nucleobase with 7, 8‐difluoro‐ 3, 4‐dihydro‐3‐methyl‐2H‐[1, 4]benzoxazine (conjugated directly or through an aminohexanoyl spacer) was synthesized using an enzymatic transglycosylation reaction. ( S )‐4‐[2‐Amino‐9‐(β‐ D ‐ribofuranosyl)‐purin‐6‐yl]‐7, 8‐difluoro‐3, 4‐dihydro‐3‐methyl‐2 H ‐[1, 4]‐benzoxazine exhibit significant antiviral activity (SI > 32) on the model of herpes simplex virus type 1 in vitro, including an acyclovir‐resistant virus strain.